Punishment within Prison: An Examination of the Influences of Prison Officials' Decisions to Remove Sentencing Credits. Issue 1 (March 2017) - Steiner, Benjamin; Cain, Calli M.
Abstract : Despite considerable research directed toward understanding the factors that affect punishment decision‐making leading to imprisonment, few studies have examined the influences of punishment decisions within prisons. Punishment decisions made within prisons can affect an individual's liberty during their imprisonment and/or the timing of their release from prison if the punishment results in the loss of sentencing credits or influences parole decision‐making. Moreover, if punishment disparities result from these decisions, then some offender groups may endure a greater loss of liberty relative to others. In this study, we examine the factors that influence prison officials' decisions to remove sentencing credits in response to prison rule violations. Analysis of collected data from a Midwestern state prison system reveal that prison officials are primarily influenced by the seriousness and type of the rule violation, along with an inmate's violation history. Other relevant factors include those proximately connected to an inmate's risk of subsequent misbehavior such as gang membership and those that are linked to practical consequences and constraints associated with the organizational environment and particular inmates such as the proportion of their sentence an inmate has served and whether an inmate has mental health problems.